THE MEANING OF ALPHA FEMALE IN FEMALE LIBRARIAN: Building a Positive Image of Libraries through Female Librarians as Alpha Female - Yunus Winoto; Tine Silvana Rachmawati (Pusat Kajian Humaniora FBS Universitas Negeri Padang, 2017)
MAKNA DIRI ALPHA FEMALE PADA PUSTAKAWAN PEREMPUAN:Membangun Citra Positif Perpustakaan Melalui Kiprah Pustakawan Perempuan Sebagai Alpha FemaleAbstractThe profession of librarians is often associated with women. This can be justified if we refer to data and research results that have been done in several countries. However, many women who work in the library, this does not necessarily describe that library work is a simple and easy job. However, on the contrary, work in the field of library is increasingly complex and demands the competence and mastery of information technology. Moreover, the expectations of some users who demand a fast and quality service. Therefore to answer this problem required a female librarian who has the competence, intelligent and able to become a leader for his group and can show the characteristics as a professional. As for the description of people like this people call it with the term alpha female. With the birth of alpha female figures among female librarians is expected to change the positive image of librarians and library institutions. This is because the female alpha figure in the female librarian is a figure of women who are considered